2023
DOI: 10.3390/biomedicines11030778
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Dysregulated Immune Response in Severe Forms of COVID-19 and Bacterial Sepsis via Single-Cell Transcriptome Sequencing

Abstract: Critically ill COVID-19 patients start developing single respiratory organ failure that often evolves into multiorgan failure. Understanding the immune mechanisms in severe forms of an infectious disease (either critical COVID-19 or bacterial septic shock) would help to achieve a better understanding of the patient’s clinical trajectories and the success of potential therapies. We hypothesized that a dysregulated immune response manifested by the abnormal activation of innate and adaptive immunity might be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Notably, there is a high incidence of lymphopenia affecting both B and T cell populations, with subsequent impacts on cellular and humoral responses. Furthermore, studies have also indicated the presence of monocyte dysfunction, whose intensity seemingly correlates with disease severity [ 42 , 43 , 44 , 45 ]. These immune alterations collectively contribute to the development of an immunodeficient state intrinsically linked to COVID-19, thereby rendering severe COVID-19 patients more susceptible to MDR infections.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Notably, there is a high incidence of lymphopenia affecting both B and T cell populations, with subsequent impacts on cellular and humoral responses. Furthermore, studies have also indicated the presence of monocyte dysfunction, whose intensity seemingly correlates with disease severity [ 42 , 43 , 44 , 45 ]. These immune alterations collectively contribute to the development of an immunodeficient state intrinsically linked to COVID-19, thereby rendering severe COVID-19 patients more susceptible to MDR infections.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The innate immune system has the crucial role of recognizing the virus and activate inflammatory pathways in order to mount an effective antiviral response and viral clearance [ 3 ]. However, evidence has shown the heterogeneity of the immune response in severe COVID-19, which can exhibit hyperinflammatory and/or immunosuppressive phenotypes in effector cells [ 2 , 4 , 5 , 6 , 7 ]. Limited studies have suggested that this altered innate immune response seems to be patient-dependent [ 2 ] and the different outcomes of SARS-CoV-2 infection may be influenced by preexisting comorbidities [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%